Becoming a Smart User in the Social Media Era - Dahlena, Alni; Septiani, Rina; Adiansyah, Adi; Isnawati, Isnawati; Mulyana, Eldi; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Indonesian Journal of Community Empowerment (IJCE), 2024)
Problems in the decline in communication ethics that occur in social media in the current situation, certainly make many parties think that the negative impact of technology has dominated, which has caused the erosion of politeness norms in communication, thus giving a bad influence on society, especially the younger generation. The purpose of this training is to provide information literacy for the public to implement wise efforts to use social media. This training method is carried out by delivering material, question and answer sessions and evaluation. The results of this training can be interpreted that in an effort to implement policies and ethics when using social media, many benefits will be felt from social media. So that social media can be used for activities in information literacy, many people also get information on health, employment, and so on more easily thanks to social media. It all depends on each individual, and of course these individuals understand the ethics of social media. Therefore, people can use social media wisely in accordance with applicable regulations.